Casa Floor Enterprise / Khairunnisa Abd Murad ... [et al.] - Abd Murad, Khairunnisa; Hassim, Hartini; Tajuddin, Nor Hafizah; Ain Mat Aris, Yang Emirza (2003)
Casa Floor is a company which give customers services of installing laminate wooden floor. Since this product is very new to the customers in Pulau Pinang, Alor Setar, Sungai Petani as well as Perlis.